Role of Carbon Dioxide in Catabolism of Propane by “Nocardia paraffinicum” (Rhodococcus rhodochrous) - MacMichael, Gregory J. (1987)
The catabolism of propane by “Nocardia paraffinicum” (Rhodococcus rhodochrous) has been shown to involve CO(2) fixation after its oxidation to propionic acid. “N. paraffinicum” failed to grow on either propane or 1-propanol in the absence of CO(2). The rate of propane utilization was directly related to the initial CO(2) concentration, and Warburg respirometry suggested that CO(2) was required for the catabolism of 1-propanol, propionaldehyde, and propionate but not for 2-propanol. These data also suggested that the predominant pathway for the utilization of propane by “N. paraffinicum” was through 1-propanol. The use of [2-(14)C]propane and (14)CO(2) confirmed the catabolism of propane and the fixation of CO(2). Through the use of these isotopes and the pyruvate carboxylase inhibitor sodium arsenite, the labeled 2,4-dinitrophenylhydrazine derivative of pyruvate was trapped and isolated via thin-layer chromatography. The trapping of [(14)C]pyruvate in this manner was considered to be indicative of the presence of the methylmalonyl coenzyme A pathway for CO(2) fixation.